The Use of PlantNet Identify for Identifying Arecaceae Family Plants in Biology Learning Among Biology Education Students at Universitas Labuhanbatu - Meliani Simbolon; Khairul; Novi Fitriandika Sari (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to examine the use of the PlantNet Identify application in identifying higher plants of the Arecaceae family in biology learning among Biology Education students at Universitas Labuhanbatu. The study employed a descriptive quantitative approach, involving 21 Biology Education students selected using a total sampling technique. The data were primary data collected through an online questionnaire distributed via Google Forms, with the use of the PlantNet Identify application as the independent variable (X) and the identification of higher plants of the Arecaceae family as the dependent variable (Y). The results of the simple linear regression analysis indicated no significant relationship between the use of the PlantNet Identify application and students’ ability to identify higher plants of the Arecaceae family, with a significance value of 0.357 (p > 0.05). The R² value further showed that the application contributed only 4.48% to students’ identification ability. These findings indicate that there is no strong correlation between the use of PlantNet Identify and students’ ability to understand plants belonging to the Arecaceae family. However, the results of this study are limited by the small sample size.